Literature-Based Education Figure Islam as an Effort to Develop Islamic Character in Children in The 4.0 Era - Yeri Utami; Monita Nur Shabrina; Tya Anggraini (Indonesian Journal of Early Childhood Education Studies, 2023)
The 4.0 or often referred to as the z generation (net) is an extremely close generation with the technological sophistication capable of presenting various forms of information in both positive and negative forms easily and openly. This surely requires special attention from parents, teachers, and the community in watching over children so as not to be susceptible to the negative information they receive. Good character children are at stake if they cannot use technology wisely. The emergence of cases of moral or destructive degradation is one of the results of the misuse of the information technology. The purpose of this study is to discuss how the effort can be made to prevent children from falling into the adverse effects of modern technological sophistication is to develop islamic character as a foundation for children's development through literally-based education toward the islamic figure. The writer use the library reseach approach to obtain data and information on the literary-based education of a figure of Islam as an effort to develop the child content of the relevant literature. So the end result of this study was to theorize about how education-based islamists developed the character of islamic children in 4.0.